The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.4070/kcj.2006.36.5.329
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Resynchronization Therapy: Biventricular Pacing

Abstract: Although the estimates from limited studies vary on the proportion of patients with heart failure who also have ventricular dyssynchrony as reflected by a prolonged QRS complex, often in the form of left bundle branch block, the number of such patients is large (27% to 53%) and it is certainly in excess of the rate for the general population. Among these patients, 10% to 15% are candidates for cardiac resynchronization therapy (CRT) via biventricular pacing. Accumulated evidence from randomized controlled stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Prolonged ventricular dyssynchrony induced by long-term RVP is associated with deleterious LV remodeling, which are LV dilatation and LV asymmetrical hypertrophy ( 2 , 8 , 9 ). A recent small series study documented that CRT was effective in improving LV function in young patients with RVP induced cardiomyopathy ( 10 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged ventricular dyssynchrony induced by long-term RVP is associated with deleterious LV remodeling, which are LV dilatation and LV asymmetrical hypertrophy ( 2 , 8 , 9 ). A recent small series study documented that CRT was effective in improving LV function in young patients with RVP induced cardiomyopathy ( 10 , 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the correction of ventricular asynchrony is an attractive treatment goal, and the methods for evaluating ventricular asynchrony are of great interest for obtaining the prognosis and optimizing therapy for HF patients. 2)3) QRS prolongation usually indicates impaired propagation of the electrical input, and this is frequently associated with increased morbidity and mortality of HF patients. 4)5) However, the recent data has demonstrated that mechanical asynchrony is not necessarily related to electrical asynchrony.…”
Section: Introductionmentioning
confidence: 99%